Iron Deficiency in Patients with Advanced Heart Failure - Bakosova, Maria; Krejci, Jan; Godava, Julius; Ozabalova, Eva; Poloczkova, Hana; Honek, Tomas; Hude, Peter; Machal, Jan; Bedanova, Helena; Nemec, Petr; Spinarova, Lenka (Medicina, 2022)
Background and Objectives: Iron deficiency (ID) is a common comorbidity in patients with heart failure. It is associated with reduced physical performance, frequent hospitalisations for heart failure decompensation, and high cardiovascular and overall mortality. The aim was to determine the prevalence of ID in patients with advanced heart failure on the waiting list for heart transplantation. Methods and Materials: We included 52 patients placed on the waiting list for heart transplantation in 2021 at our centre. The cohort included seven patients with LVAD (left ventricle assist device) as a bridge to transplantation implanted before the time of results collection. In addition to standard tests, the parameters of iron metabolism were monitored. ID was defined as a ferritin value <100 μg/L, or 100-299 μg/L if transferrin saturation (T-sat) is <20%. Results: ID was present in 79% of all subjects, but only in 35% of these patients anaemia was expressed. In the group without LVAD, ID was present in 82%, a median (lower-upper quartile) of ferritin level was 95.4 (62.2-152.1) μg/mL and mean T-sat was 0.18 ± 0.09. In LVAD group, ID was present in 57%, ferritin level was 268 (106-368) μg/mL and mean T-sat was 0.14 ± 0.04. Haemoglobin concentration was the same in patients with or without ID (133 ± 16) vs. (133 ± 23). ID was not associated with anaemia defined with regard to patient's gender. In 40.5% of cases, iron deficiency was accompanied by chronic renal insufficiency, compared to 12.5% of the patients without ID. In the patients with LVAD, ID was present in four out of seven patients, but the group was too small for reliable statistical testing due to low statistical power. Conclusions: ID was present in the majority of patients with advanced heart failure and was not always accompanied by anaemia and renal insufficiency. Research on optimal markers for the diagnosis of iron deficiency, especially for specific groups of patients with heart failure, is still ongoing.
Keywords: Anemia, Iron-Deficiency; Ferritins; ferritiny; Humans; deficit železa; Anemia; Heart Failure; lidé; srdeční selhání; Iron Deficiencies; anemie z nedostatku železa; anemie